(untitled) (BIRDEM Medical Journal, 2020)
Background: During period of critical illness, there are diverse alterations in the hypothalamus-pituitarythyroid (HPT) axis. This diversity in critically ill patients and the etiological relationship between underlying disease and non-thyroidal illness (NTI) is poorly understood. The aims of this study were to examine the features of NTI and outcomes in critically ill patients admitted in Critical Care Medicine (CCM) Department, BIRDEM General Hospital. Methods: A total of 86 patients admitted to CCM department, BIRDEM General Hospital during the period of July to December 2015 , having nonthyroidal illness, detected by thyroid function tests during ICU stay were enrolled in this study. All patients discharged from hospital were followed up for a period of 6 months. Patients with known thyroid diseases or taking medications that affect thyroid function were excluded. Condition at hospital discharge and mortality in the ICU or later at home after discharge within next 6 months was assessed as outcomes. Results: Mean age of the study subjects was 63.87(±13.5)years and 45(52.3%)of the study subjects were female. Most of the study subjects had diabetes (84.88%) and hypertension (82.55%).Mean (±SD) of FT3 (pmol/l), FT4(pmol/l), TSH (uIU/ml) were 2.85(±1.35),12.74(±8.17) and 2.81(±8.57)respectively. Among the total study subjects 44.18% patients died in ICU and 2.32% patients after shifting to ward. Among the patients having pneumonia, Myocardial Infarction(MI) /Arrhythmia, Stroke, Sepsis and Gastrointestinal disease, 50.94% 51.02%, 56.0%,53.85%,37.50% died in hospital (ICU or after shifting toward).The 46 patients ,who were discharged from hospital were followed up for next 6 months. Conclusion: NTI is a transient adaptive response affecting individuals with acute and chronic illness and is more common among patients admitted in intensive care unit (ICU). The prognosis of patients having NTI depends on severity of thyroid dysfunction. Birdem Med J 2021; 11(1): 47-51